2017
DOI: 10.5897/ajpp2017.4820
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the colo-protective effects of tadalafil in an experimental model of ulcerative colitis in rats

Abstract: Ulcerative colitis is a serious premalignant condition with a confusing multifactorial pathogenesis. It should warrant all attention by researchers, for exploration of new prophylactic or therapeutic drugs targeting its pathophysiology. The current study was conducted to study the possible role of tadalafil and its potential actions in ulcerative colitis rat model, induced by acetic acid. Forty eight male Wistar albino rats were classified into 6 groups: control group, acetic acid (AA)-ulcerated group, AA-ulce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Futhermore, experimental studies suggested that PDE5 inhibitor tadalafil and sildenafil are capable to retard UC. The mechanism involves in the suppression of inflammatory cytokines, oxidative stress, apoptosis, and improving the intestinal barrier function (Islam et al, 2017;Labib et al, 2017). Since PDE9 has the similar characteristic of PDE5, with the higher affinity for cGMP (Fisher et al, 1998), meanwhile, our previous study had shown that DSS induces the highest expression of PDE9 among the PDE superfamily (Supplementary Figure S1) So, we speculated that PDE9 inhibitor could also be a good candidate to attenuate UC.…”
Section: Introductionmentioning
confidence: 97%
“…Futhermore, experimental studies suggested that PDE5 inhibitor tadalafil and sildenafil are capable to retard UC. The mechanism involves in the suppression of inflammatory cytokines, oxidative stress, apoptosis, and improving the intestinal barrier function (Islam et al, 2017;Labib et al, 2017). Since PDE9 has the similar characteristic of PDE5, with the higher affinity for cGMP (Fisher et al, 1998), meanwhile, our previous study had shown that DSS induces the highest expression of PDE9 among the PDE superfamily (Supplementary Figure S1) So, we speculated that PDE9 inhibitor could also be a good candidate to attenuate UC.…”
Section: Introductionmentioning
confidence: 97%
“…In a study, Marcus et al showed that vardenafil inhibited myofibroblast transformation, collagen gel contraction and extracellular matrix production in a rat model of Peyronie's Disease [19]. In other studies, it was shown that tadalafil can reduce hepatic and circulating levels of TNF-and limit the upregulation of proinflammatory cytokines [20][21][22]. Yildirim et al reported that sildenafil lowered MDA levels and corrected antioxidant glutathione in a pulmonary fibrosis model (bleomycin-treated rats) [23].…”
Section: Discussionmentioning
confidence: 99%